Black lives matter to Jesus : the salvation of Black life and all life in Luke and Acts - Jerkins, Marcus (Fortress Press, 2021)
Black-skinned people were and are included in the family of God, demonstrating that all colors in the family of God have dignity. This view bolsters a Christian anti-racist agenda. This work attempts to undermine Christian racism that has deemed Black skin inherently problematic, showing that the destruction of racism is at the heart of the gospel of Jesus. --